An Academic Map of Social Entrepreneurship in Taiwan - Kubátová, Jaroslava; Horálek, Adam; Kosina, David; Kročil, Ondřej (Univerzita Palackého v Olomouci, 2022)
The purpose of the paper is to map academic publications on social entrepreneurship in Taiwan. Mapping review, a specific type of literature review, was conducted to gain this purpose. The texts of the abstracts of the reviewed publications were analyzed manually, and the full texts with the use of an online text analysis tool Sketch Engine in order to find the research topics in the field and their structure. It was found that a significant research topic concerns social entrepreneurial intentions, but also several unique innovative research topics were identified. The findings are particularly useful for comparative research in other countries, including the Czech Republic, but also inspiring for social entrepreneurs. Research limitations are discussed in the paper and have to be taken into consideration in relation to the research outcomes.
Akademická mapa sociálního podnikání na Tchaj-wanu
Keywords: social entrepreneurship; Taiwan; text analysis; sociální podnikání; Tchaj-wan; textová analýza